Assessing the utility and accuracy of ICD10‐CM non‐traumatic subarachnoid hemorrhage codes for intracranial aneurysm research. Issue 4 (5th January 2021) - Roark, Christopher; Wilson, Melissa P.; Kubes, Sheila; Mayer, David; Wiley, Laura K.
Abstract: Background: The 10th revision of International Classification of Disease, Clinical Modification (ICD10‐CM) increased the number of codes to identify non‐traumatic subarachnoid hemorrhage from 1 to 22. ICD10‐CM codes are able to specify the location of aneurysms causing subarachnoid hemorrhage (aSAH); however, it is not clear how frequently or accurately these codes are being used in practice. Objective: To systematically evaluate the usage and accuracy of location‐specific ICD10‐CM codes for aSAH. Methods: We extracted all uses of ICD10‐CM codes for non‐traumatic subarachnoid hemorrhage (I60.x) during the first 3 years following the implementation of ICD10‐CM from the billing module of the electronic health record (EHR) for UCHealth. For those codes that specified aSAH location (I60.0‐I60.6), EHR documentation was reviewed to determine whether there was an active aSAH, any patient history of aSAH, or unruptured intracranial aneurysm/s and the locations of those outcomes. Results: Between 1 October 2015 and 30 September 2018, there were 3119 instances of non‐traumatic subarachnoid hemorrhage ICD10‐CM codes (I60.00‐I60.9), of which 297 (9.5%) code instances identified aSAH location (I60.0‐I60.6). The usage of location‐specific codes increased from 5.7% in 2015 to 11.2% in 2018. These codes accurately identified current aSAH (64%), any patient history of aSAH (84%), and any patient history of intracranial aneurysm (87%). The accuracy of identified outcome location was 53% in current aSAH, 72% for any history of aSAH, and 76% for any history of an intracranial aneurysm. Conclusions: Researchers should use ICD10‐CM codes with caution when attempting to detect active aSAH and/or aneurysm location.